Evaluation of complex multi-physics phenomena at gas diffusion electrodes during high-pressure water electrolysis with AEMs - Erik Delp; Rakesh Mishra; Enno Wagner (Scientific Reports)
Abstract The alkaline water electrolysis is a well-established process for producing green hydrogen from renewable energy sources. With up-to-dateAEM electrolyzers, electrochemical gas compression can be realized with water electrolysis and ion pumping membranes, to avoid costly mechanical compression. In this experimental study, we researched an electrolyzer cell with a strong metal structure, for internal pressure difference of up to 100 bar. Micro-porous gas diffusion electrodes containing non-precious nickel catalysts as well as different separators, alkaline membranes and AEMs have been investigated in the range of 300 to 800 mA cm− 2. For one preferred AEM, characteristics are shown for hydrogen pressures between 20 and 80 bars, while the anode remains at ambient 1 bar. Impedance spectroscopy diagrams are used to display the individual cell components: the ohmic resistance of the AEM and the complex impedances of both electrodes. Therewith, we could visualize the complex multi-physics phenomena and show that the oxygen electrode works as a Wartburg-element, especially due to higher diffusion rates and therewith entropy production during bubble formation.